ICT factors and lecturers' productivity in public colleges of education in the new normal (2021)
The outbreak of COVID-19 pandemic introduced a new normal into the business world and the higher education environment. The pandemic has served as an existential threat to humanity resulting in productive dynamism in higher education system particularly in the demand for enhanced productivity of lecturers through Information Communications Technology (ICT) factors (availability, accessibility and functionality of ICT facilities). This study investigated ICT factors and the productivity of lecturers in public Colleges of Education in Nigeria in the new normal. The study was guided by one research question and one hypothesis. The survey research design was adopted for the study. The population for the study comprised of lecturers and students in Colleges of Education in the Southwestern geopolitical zone of Nigeria. The multi-stage procedure was adopted to draw a sample of 1,011 Lecturers and 3,033 students. The findings of the study included the fact that ICT facilities are available, accessible and functional in public Colleges of Education in Southwestern Nigeria as they scored low (ẋ = 0.00-2.44). Also, it was found from the hypothesis in this study that a significant relationship exists between ICT facilities factors (availability, accessibility, functionality) and lecturers’ productivity (teaching) in public Colleges of Education in Southwestern Nigeria at r=0.125; 0.868 and 0.824; p<0.05 level of significance. The study recommended that Government should make sure that acquisition of computers and other related ICT facilities are available, adequately accessible for lecturers and functioning properly. Additionally, training of lecturers to enhance ICT proficiency must be encouraged by the government.